A Global Vector Autoregression (GVAR) model for regional labour markets and its forecasting performance with leading indicators in Germany - Norbert Schanne (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2015)
It is broadly accepted that two aspects regarding the modeling strategy are essential for the accuracy of forecast: a parsimonious model focusing on the important structures, and the quality of prospective information. Here, we establish a Global VAR framework, a technique that considers a variety of spatio-temporal dynamics in a multivariate setting, that allows for spatially heterogeneous slope coefficients, and that is nevertheless feasible for data without extremely long time dimension. Second, we use this framework to analyse the prospective information regarding the economy due to spatial co-development of regional labour markets in Germany. The predictive content of the spatially interdependent variables is compared with the information content of various leading indicators which describe the general economic situation, the tightness of labour markets and environmental impacts like weather. The forecasting accuracy of these indicators is investigated for German regional labour-market data in simulated forecasts at different horizons and for several periods. Germany turns out to have no economically dominant region (which reflects the polycentric structure of the country). The regions do not follow a joint stable long run trend which could be used to implement cointegration. Accounting for spatial dependence improves the forecast accuracy compared to a model without spatial linkages while using the same leading indicator. Amongst the tested leading indicators, only few produce more accurate forecasts when included in a GVAR model, than the GVAR without indicator. – – Zwei Aspekte bezüglich der Modellierungsstrategie werden gemeinhin als entscheidend für die Genauigkeit von Prognosen betrachtet: Einerseits ein in den zu schätzenden Parametern sparsames Modell, welches nur die wichtigsten Zusammenhänge abdeckt; andererseits die Aussagekraft der vorausschauenden Information. Hier wird ein Mehrregionenmodell ähnlich einem Globalen Vektorautoregressiven (GVAR) Ansatz entwickelt. Diese Technik berücksichtigt verschiedene Strukturen der räumlich-zeitlichen Dynamik in multivariaten Gleichungssystemen, sie erlaubt regional heterogene Parameter und ist dennoch auch für Daten ohne sehr langen Beobachtungszeitraum geeignet. In diesem Modellrahmen werden regionale Co-Entwicklungen hinsichtlich ihrer vorausschauenden Information untersucht. Der Prognosegehalt räumlicher Abhängigkeiten wird dem Informationsgehalt von vorauseilenden Indikatoren gegenübergestellt, welche die allgemeine wirtschaftliche Lage, die Knappheit im Arbeitsmarkt und Umwelteinflüsse (wie etwa das Wetter) beschreiben. Die Prognosegenauigkeit wird mit deutschen regionalen Arbeitsmarktdaten in simulierten Prognosen auf unterschiedlichen Horizonten untersucht. Die Existenz einer alle anderen bestimmenden Region wird für Deutschland abgelehnt (was die polyzentrische Struktur des Landes widerspiegelt). Die Regionen folgen keinem stabilen gemeinsamen Trend, der zur Implementierung einer Kointegrationsbeziehung genutzt werden könnte. Die Berücksichtigung regionaler Abhängigkeiten verbessert die Prognosegenauigkeit gegenüber einem Modell ohne diese, wenn derselbe vorausschauende Indikator verwendet wird. Nur wenige der geprüften Indikatoren tragen bei Berücksichtigung in einem GVAR zu einer genaueren Prognose im Vergleich zu einem GVAR ohne Indikator bei.
Keywords: C23; E24; E27; R12; 330; Cross-sectional dependence; Global VAR; Labour market forecasting; Leading indicators; Regional forecasting; Spatio-temporal dynamics